The Translation Strategies Of Slang Expressions In The Subtitle Of The Movie “My Oxford Year” - Simanullang, Yenita; Lumbantobing, Febrina S.L.; Sianturi, Srisofian (Lembaga Riset dan Inovasi Almatani, 2026)
The use of slang in movies represents informal, expressive, and culturally bound language that often creates challenges in translation, particularly in subtitles. Slang expressions are commonly used to reflect natural conversation, characterize speakers, and convey emotional nuance. However, many slang expressions do not have direct equivalents in the target language, which can result in shifts in meaning, tone, and cultural context. This issue becomes more complex when translating British slang into Indonesian, as both languages differ significantly in terms of cultural references, social usage, and linguistic structure. Therefore, it is important to examine how slang expressions are translated and what strategies are applied to maintain their meaning and function in subtitles. This study aims to identify the types of slang expressions found in the movie My Oxford Year and to analyze the translation strategies used in translating those expressions into Indonesian subtitles. This study employs a qualitative descriptive method. The data were collected from the English and Indonesian subtitle files of the movie, focusing on 35 selected slang expressions that appear throughout the dialogue. The data were analyzed using classification of slang by Tony Thorne and translation strategies by Mona Baker. The findings reveal that various types of slang are used in the movie, including colloquial slang, taboo slang, youth slang, occupational slang, and creative or innovative slang, with colloquial slang as the most dominant type. In terms of translation strategies, paraphrase using related words, cultural substitution, and translation by a more neutral word are the most frequently applied strategies. Overall, the study indicates that the translator tends to prioritize clarity, readability, and naturalness in the target language, although some stylistic and cultural nuances of the original slang expressions are inevitably reduced.